2018
DOI: 10.1093/nar/gky1177
|View full text |Cite
|
Sign up to set email alerts
|

Binding of cellular nucleolin with the viral core RNA G-quadruplex structure suppresses HCV replication

Abstract: Hepatitis C virus (HCV) infection is a major cause of human chronic liver disease and hepatocellular carcinoma. G-quadruplex (G4) is an important four-stranded secondary structure of nucleic acids. Recently, we discovered that the core gene of HCV contains a G4 RNA structure; however, the interaction between the HCV core RNA G4 and host cellular proteins, and the roles of the HCV core RNA G4 in HCV infection and pathogenesis remain elusive. Here, we identified a cellular protein, nucleolin (NCL), which bound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 57 publications
5
49
0
1
Order By: Relevance
“…Viral G4 also associated with host proteins. Cellular nucleolin interacted with viral core G4 to suppress HCV replication (Bian et al, 2019). Nucleolin directly binds to EBV G4 in EBNV1 mRNA sequence to inhibit EBNV1 protein expression (Lista et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Viral G4 also associated with host proteins. Cellular nucleolin interacted with viral core G4 to suppress HCV replication (Bian et al, 2019). Nucleolin directly binds to EBV G4 in EBNV1 mRNA sequence to inhibit EBNV1 protein expression (Lista et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, nucleolin silencing was directly correlated with increased HCV RNA expression. 48 These results strongly suggest the existence of a host anti-viral immunity mechanism involving G4 structures. Additional bioinformatic studies based on a different algorithm showed the presence of a very interesting G4-forming sequence in the stem-loop IIy of the HCV negative strand, precisely in the 3'-UTR, which is the initiation site for the (+)-strand replication.…”
Section: Flavivirusesmentioning
confidence: 77%
“…The one located in the core gene was characterized as the most stable G4. 48 Its stabilization with the G4 ligands TMPyP4 and a PDS derivative (PDP) promoted viral RNA-dependent RNA polymerase stalling, with consequent reduction in HCV core protein levels. In vivo analysis revealed that PDP led to G4-mediated antiviral activity in the low micromolar range, by inhibiting intracellular replication of different HCV genotypes.…”
Section: Flavivirusesmentioning
confidence: 99%
“…Huh7.5.1 cells were cultured in complete DMEM (Thermo Fisher Scientific, Waltham, MA, USA) with 10% fetal bovine serum (FBS, HyClone, Logan, USA). Expansion of cell culture-derived HCV (HCVcc, genotype 2a, Japanese fulmi-nant hepatitis 1, JFH1 isolate) was performed using Huh7.5.1 cells as described in our previous publication [38]. In brief, Huh7.5.1 cells were infected with HCVcc (MOI of ß1; 1 × 10 7 RNA copies/mL).…”
Section: Plasmids Virus and Cell Culturementioning
confidence: 99%